A Rare Case of a Primary Squamous Cell Carcinoma of the Stomach Presenting as a Submucosal Mass - Wolf von Waagner; Zhuo Wang; Antonio I. Picon (Case Reports in Surgery)
We report a case of a 70-year-old man, with a status after aortic valve replacement, who presented with melena and hypotension. On physical examination, he was hypotensive, but he responded to resuscitation. Esophagogastroduodenoscopy revealed a submucosal mass in the gastric fundus. Imaging of the chest, abdomen, and pelvis showed no evidence of local or distant metastasis. He underwent a partial diaphragmatic resection, gastrectomy, lymphadenectomy, and Roux-en-Y esophagojejunostomy. Pathology showed a gastric squamous cell carcinoma (SCC) invading the diaphragm, with negative margins of resection, and one positive perigastric lymph node. He received chemoradiation, but the patient expired 27 months after surgery.